Dysgerminoma and granulosa cell tumor in a bitch - Oliveira, Ayisa R.; Flecher, Mayra C.; Jabour, Flávia F.; Souza, Tayse D.; Hardt, Isabela; Vieira, Fernanda T.; Rassele, Alice C.; Vicente, Gabriel C.; Machado, Flávia M. (Brazilian Journal of Veterinary Pathology, 2016)
Dysgerminoma and granulosa cell tumor are neoplasms of the ovary of domestic animals, originating from germ cells and sex-cords cells, respectively. These neoplasms generally occur unilaterally, and usually as a single neoplasm. This report describes a case of a dysgerminoma in the right ovary and a granulosa cell tumor in the left ovary in a six years old bitch. An Akita and Siberian Husky crossbred bitch was admitted at the Veterinary Hospital (Universidade Vila Velha), with a history of purulent vaginal discharge, irregular estrous cycle, fatigue, polydipsia and polyuria. Ultrasound exam demonstrated bilateral ovarian neoplasms, and the animal was subjected to ovariohysterectomy. Macroscopic and microscopic features found in right and left ovaries were typical of dysgerminoma and granulosa cells tumor Sertoli-like, respectively. The uterus had cystic endometrial hyperplasia associated with mild metritis. Ovarian neoplasms occurring bilaterally are uncommon especially with different cell origins and distinct histopathological patterns in each ovary as described in this report.